Current Steering Using Multiple Independent Current Control Deep Brain Stimulation Technology Results in Distinct Neurophysiological Responses in Parkinson’s Disease Patients - Peeters, Jana; Boogers, Alexandra; Van Bogaert, Tine; Gransier, Robin; Wouters, Jan; Nuttin, Bart; Mc Laughlin, Myles (Frontiers in Human Neuroscience, 2022)
Background Deep brain stimulation (DBS) is an effective neuromodulation therapy to treat people with medication-refractory Parkinson’s disease (PD). However, the neural networks affected by DBS are not yet fully understood. Recent studies show that stimulating on different DBS-contacts using a single current source results in distinct EEG-based evoked potentials (EPs), with a peak at 3 ms (P3) associated with dorsolateral subthalamic nucleus stimulation and a peak at 10 ms associated with substantia nigra stimulation. Multiple independent current control (MICC) technology allows the center of the electric field to be moved in between two adjacent DBS-contacts, offering a potential advantage in spatial precision. Objective Determine if MICC precision targeting results in distinct neurophysiological responses recorded via EEG. Materials and Methods We recorded cortical EPs in five hemispheres (four PD patients) using EEG whilst employing MICC to move the electric field from the most dorsal DBS-contact to the most ventral in 15 incremental steps. Results The center of the electric field location had a significant effect on both the P3 and P10 amplitude in all hemispheres where a peak was detected (P3, detected in 4 of 5 hemispheres, p < 0.0001; P10, detected in 5 of 5 hemispheres, p < 0.0001). Post hoc analysis indicated furthermore that MICC technology can significantly refine the resolution of steering. Conclusion Using MICC to incrementally move the center of the electric field to locations between adjacent DBS-contacts resulted in significantly different neurophysiological responses that may allow further precision of the programming of individual patients.